2015
DOI: 10.18006/2015.3(3).298.306
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and biochemical effects of aspartame intake in rats under an experimental diet

Abstract: The present study evaluates the effect of aspartame intake in rats under a diet mimicking the trends of fat consumption in the society. The composition of the experimental diet was within the recommended human limits except the saturated fat amount supplying from coconut fat. Rats under the experimental diet showed an increase in the body weight, transitory increase in the blood pressure and in plasma values of glucose and triglycerides alongside a transitory reduction in plasma urea versus the standard group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Aspartame with its metabolite methanol could have the same effect of ethanol in the long-term, as ethanol blocks the apical exocytosis of pancreatic acini redirecting it toward the basolateral plasma membrane, causing interstitial pancreatitis, damage to the subcellular membrane, and release of proteolytic enzymes that may lead to auto-digestion [31]. In contrary to that, Martinez-Morales et al [32] found that aspartame administration to experimental diet did not show any increase in blood glucose and TGs level.…”
Section: : Photomicrographs Of H and E Staining Of Liver Tissue: (A-d...mentioning
confidence: 98%
“…Aspartame with its metabolite methanol could have the same effect of ethanol in the long-term, as ethanol blocks the apical exocytosis of pancreatic acini redirecting it toward the basolateral plasma membrane, causing interstitial pancreatitis, damage to the subcellular membrane, and release of proteolytic enzymes that may lead to auto-digestion [31]. In contrary to that, Martinez-Morales et al [32] found that aspartame administration to experimental diet did not show any increase in blood glucose and TGs level.…”
Section: : Photomicrographs Of H and E Staining Of Liver Tissue: (A-d...mentioning
confidence: 98%
“…Harvey's sarcoma of rat viral homozygous h-Ras and viral homologous myeloma c-myc in rat livers [13]. Several clinical disorders, including hepatotoxicity, nephrotoxicity, neurotransmitter imbalance, and cognitive impairment [14]. Measurement of the activities of these marker enzymes in tissues and body fluids can be used to assess the degree of damage and toxicity of a chemical compound on organs/tissues [15,16].…”
Section: Introductionmentioning
confidence: 99%